Penggunaan Media Sosial dalam Meningkatkan Penjualan Melalui Aplikasi TikTok: Studi Kasus pada Industri E-Commerce - Nakita Sisilia; Rayyan Firdaus (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
Abstract: Social media is one form of developing information technology and social media users can share various information through various platforms such as TikTok. TikTok has proven to be an effective platform in promotion and marketing strategies, increasing public awareness and business revenue. Features such as short videos, filters, and creative ads allow users to reach a wide audience. However, it is also necessary to be aware of negative impacts such as gadget addiction and controversial content. Strategies to increase TikTok's effectiveness include engaging content, collaboration with influencers, use of hashtags, and ads such as Top View Ads and Brand Takeover. With the right approach, TikTok can be a very effective promotional tool to increase sales and consumer interaction in e-commerce.